Long period gratings written into a photonic crystal fibre by a femtosecond laser as directional bend sensors - Allsop, Thomas P.; Kalli, Kyriacos; Zhou, Kaiming; Lai, Yicheng; Smith, Graham N.; Dubov, Mykhaylo V.; Webb, David J.; Bennion, Ian (My University, 2008)
A series of symmetric and asymmetric LPGs were inscribed in photonic crystal fibre by a low repetition rate femtosecond laser system. The asymmetric LPGs were found to be spectrally sensitive to bend orientation, with some of the attenuation bands producing both red and blue wavelength shifts, whilst the symmetric devices produced only a unidirectional wavelength shift. Both sets of devices displayed strong polarisation dependence.
Keywords: Photonic crystals; Femtosecond laser